2013
DOI: 10.1007/s10689-013-9647-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of the BRCA1 promoter polymorphism rs11655505 with the risk of familial breast and/or ovarian cancer

Abstract: Germline mutations in the BRCA1 tumor suppressor gene predispose affected individuals to breast cancer; however, incomplete cancer penetrance and the presence of phenocopies in BRCA1 families also indicate genetic and environmental modifiers of breast cancer risk. In this study, we have tested the single nucleotide polymorphism rs1655505 of the BRCA1 promoter, as candidate for the modifier of breast cancer risk. The polymorphic variants were genotyped in BRCA1-negative (729), familial breast and/or ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Of notice, these findings parallel the recent findings by Hitchins and colleagues described above [38] with respect to MLH1 methylation in a colorectal cancer family. Notably, while BRCA1 promoter variants influencing breast and ovarian cancer risk have been reported earlier [141, 142], the finding by Evans et al is the first to link such variants to BRCA1 methylation status.…”
Section: Normal Tissue Brca1/2 Methylation and Risk Of Breast And Ovamentioning
confidence: 95%
“…Of notice, these findings parallel the recent findings by Hitchins and colleagues described above [38] with respect to MLH1 methylation in a colorectal cancer family. Notably, while BRCA1 promoter variants influencing breast and ovarian cancer risk have been reported earlier [141, 142], the finding by Evans et al is the first to link such variants to BRCA1 methylation status.…”
Section: Normal Tissue Brca1/2 Methylation and Risk Of Breast And Ovamentioning
confidence: 95%
“…Several recent studies suggested the possible of gene polymorphism (Bielinska et al, 2013;Liu et al, 2013;Ramalhinho et al, 2013) or JAK2/STAT3 pathway alteration (Teng et al, 2013) as the risk of breast cancer in population. In addition to genetic factors, there are a number of distinctive environmental that may contribute to the variable rates of incidence in this population.…”
Section: 3815 Age Distribution Of Breast Cancer From a Thailand Popumentioning
confidence: 99%
“…Our study did not exclude the possible contribution of other SNPs within this gene in BC nor substantial contribution These studies had NOS scores of 6 to 9 and assessed rs11655505 [9, [13][14][15][16], rs1799966 [4,8,17], rs3737559 [10,18], rs1799950 [8,10,17,19,20], rs799917 [4,17,[21][22][23] or rs16941 [17,24]. Assessment of genotype distribution in control groups of all included researches showed their compliance with HWE.…”
Section: Resultsmentioning
confidence: 99%